Thrift store saints: meeting Jesus 25 cents at a time - Knuth, Jane F. (Loyola Press, 2010)
A thrift store in inner-city Kalamazoo, Michigan. Exactly the place where you'd expect to meet Jesus, right? Knuth's church-going background had not prepared her for the soul-stirring experiences she experienced there. By serving the poor, they gave her much more than she could ever give them